Strategic Liquidation in Financial Crises: A Qualitative Review of Externalities and Optimal Insolvency Interventions - Muhammad Rizal; Ngadi Permana (LPPM STIE Kasih Bangsa, 2026)
This qualitative literature review examines the strategic role of liquidation during financial crises, with a focus on the externalities it generates and the design of optimal insolvency interventions. Synthesizing recent empirical and theoretical research, the study highlights how liquidation decisions—particularly in systemic downturns—affect broader economic stability through credit disruption, asset fire sales, and employment losses. The review finds that while prompt liquidation of non-viable firms can facilitate recovery, poorly structured interventions risk perpetuating inefficiencies and moral hazard. Comparative insights from diverse institutional contexts emphasize the need for hybrid insolvency regimes that balance liquidation with restructuring flexibility. This synthesis contributes to ongoing debates on how to enhance crisis responsiveness in insolvency law and policy design.